Cardiac valve replacement for infective endocarditis in patients with end stage renal disease on hemodialysis — A single institution experience. (February 2020) - Medicherla, Ratna C; Phair, John; Carnevale, Matthew; Jakobleff, William; Lipsitz, Evan; Scher, Larry
: Complications from vascular access are the leading cause of morbidity in the hemodialysis population. The use of tunneled catheters is associated with a greater risk of bacteremia and mortality when compared to other types of hemodialysis access. Infective endocarditis is a serious complication occurring in 2–5% of patients undergoing hemodialysis and is likely secondary to transient bacteremia from repetitive vascular access. Objective: To review outcomes in hemodialysis-dependent patients requiring cardiac valve replacement for infective endocarditis. Methods: A retrospective chart review was conducted to identify all patients who underwent valve replacement within a six-year period (January 2009–December 2014). Inclusion criteria included a diagnosis of infective endocarditis and end stage renal disease on hemodialysis. Relevant clinical information including demographics, comorbidities, valve involvement, causative organisms, and type of hemodialysis access (arteriovenous fistula, arteriovenous graft, or tunneled catheter) was collected. Results: A total of 1497 patients underwent cardiac valve replacement within the six-year period. Of these, 167 patients (11.2%) had infective endocarditis and 119 patients (7.9%) had end stage renal disease on hemodialysis. Overall 30-day mortality for valve replacement was 5.0% (75/1497). Mortality for patients with infective endocarditis was 7.2% (12/167) and for patients with end stage renal disease on hemodialysis was 10.1% (12/119). Thirty-three patients (2.2%) had infective endocarditis and end stage renal disease on hemodialysis. Of these, 12 patients were being dialyzed via arteriovenous fistula, 4 via arteriovenous graft, and 17 via tunneled catheter. Mortality occurred in 2 of 12 patients with arteriovenous fistula, 1 of 4 patients with arteriovenous graft, and 2 of 17 patients with tunneled catheter for an overall mortality of 15.2% (5/33). Conclusion: Infective endocarditis remains a significant problem in patients with end stage renal disease on hemodialysis, particularly when tunneled catheters are utilized for hemodialysis access. Although appropriate algorithms have been developed to minimize long term use of tunneled catheters, bacteremia remains a significant problem. We reviewed our institutional experience and the medical literature to determine outcomes in hemodialysis-dependent patients with infective endocarditis requiring valve replacement. Despite mortality rates between 42 and 73% reported in the literature, our mortality rate was 15.2%. 1 Care of these critically ill patients must emphasize early diagnosis and aggressive management to optimize outcomes.